Serendipitous discovery of a dying Giant Radio Galaxy associated with NGC 1534, using the murchison widefield array - Hurley-Walker, N.; Johnston-Hollitt, M.; Ekers, R.; Hunstead, R.; Sadler, E.; Hindson, L.; Hancock, P.; Bernardi, G.; Bowman, J.; Briggs, F.; Cappallo, R.; Corey, B.; et al. (Oxford University Press, 2015)
Recent observations with the Murchison Widefield Array at 185 MHz have serendipitously unveiled a heretofore unknown giant and relatively nearby (z = 0.0178) radio galaxy associated with NGC 1534. The diffuse emission presented here is the first indication that NGC 1534 is one of a rare class of objects (along with NGC 5128 and NGC 612) in which a galaxy with a prominent dust lane hosts radio emission on scales of ~700 kpc. We present details of the radio emission along with a detailed comparison with other radio galaxies with discs. NGC 1534 is the lowest surface brightness radio galaxy known with an estimated scaled 1.4-GHz surface brightness of just 0.2 mJy arcmin−2. The radio lobes have one of the steepest spectral indices yet observed: α = −2.1 ± 0.1, and the core to lobe luminosity ratio is <0.1 per cent. We estimate the space density of this low brightness (dying) phase of radio galaxy evolution as 7 × 10−7 Mpc−3 and argue that normal AGN cannot spend more than 6 per cent of their lifetime in this phase if they all go through the same cycle.